Hubungan Tingkat Pengetahuan dengan Sikap Ibu Dalam Mobilisasi Dini Pasca Sectio Cesarean - Ni Ketut Citrawati; Ni Luh Gede Rika Rahayu; Niken Ayu Merna Eka Sari (STIKes Payung Negeri Pekanbaru, 2021)
Introduction: Cesarean Section is a surgical operation for delivering a child by cutting through the wall of abdomen and uterus. Mothers after cesarean section must do early mobilization because will get many benefit, namely preventing tombosis in the leg vessels and helping the mother progress from sick dependence to health. Early mobilization is a movement, position or activity carried out by the mother after a few hours of delivery. The purpose of this study was to determine the correlation between the level of knowledge and mother's attitude in early mobilization post cesarean section in the Dara Room of RSUD Wangaya Denpasar. Method: This research is a non-experimental study with a correlational research method. The sample in this study was 35 respondents with purposive sampling technique. Result: The results showed that most respondents had a good level of knowledge, namely 16 respondents (45.7%), 14 respondents (40.0%) and less 4 respondents (14.3%). Results of data analysis with Spearman rank results obtained p = 0.000. Because the p value <α (0.05). So it can be concluded that there is correlation between the level of knowledge and mother's attitude in early mobilization post sectio cesarean in the Dara Room of RSUD Wangaya Denpasar. Discussion: Suggestions, especially mothers after cesarean section to immediately carry out early mobilization considering the importance of early mobilization after cesarean section.